PENGARUH INTENSITAS RESEARCH AND DEVELOPMENT DAN BUSINESS RISK TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN LQ45 YANG TERDAFTAR DI BEI PERIODE 2016-2020 - Yatim, Yatim; Subaida, Ida; Wahyuni, Ika (Fakultas Ekonomi dan Bisnis, 2022)
This study aims to analyze and examine the effect of research and development intensity and business risk on firm value with financial performance as the intervening variable. This research is an explanatory research. The population in this study are LQ45 companies listed on the Indonesia Stock Exchange. The sampling technique used purposive sampling technique. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM).The results of the direct influence hypothesis test using the Smart PLS 3.0 application, indicate that the intensity of research and development has a positive but not significant effect on financial performance, Business risk has a significant positive effect on financial performance, the intensity of research and development has a significant negative effect on firm value, Business risk has a positive effect but not significant to firm value, financial performance has a negative but not significant effect on firm value. The results of the indirect effect hypothesis test show that the intensity of research and development and business risk on firm value through financial performance has a negative but not significant effect.